On using students’ experiences in the classroom - Grabauskienė, A. (Psichologija, 1966)
The use of students’ experiences in the classroom is relates teaching to life. It also enables the students to use acquired knowledge in practice. Pedagogical research showed that knowledge and skills that were acquired in life experience are not assimilated by itself in the system of knowledge acquired in the classroom. Students apply in practice either knowledge acquired in learning process or they use their own life experience depending on the situation. Only engaging their experience in the knowledge system acquired in the classroom, a complex and overall knowledge system is formed. Different forms exist in the use of student experience in classroom: students give short presentations-stories during lessons about own observations, activities, etc., students compare learning material with experience, etc.